Mutation of Stevia glycosyltransferase UGT76G1 for efficient biotransformation of rebaudioside E into rebaudioside M - Jie Yu; Yehui Tao; Huayi Pan; Lei Lin; Jinyuan Sun; Ruiqi Ma; Yan Li; Honghua Jia (Journal of Functional Foods, 2022)
Rebaudioside M (RebM) is a desired natural non-caloric and high potency sweetener with very low content in the leaves of Stevia rebaudiana. In this study, based on the crystal structure of UDP-dependent glycosyltransferase UGT76G1, a key enzyme responsible for RebM production in S. rebaudiana, a computational strategy combining protein structure, molecular docking, and single-point saturation mutation was adopted to engineer UGT76G1 to promote the transformation of rebaudioside E (RebE) into RebM via a two-step continuous glycosylation. An S195Q mutant was verified to have better performance, with a catalytic efficiency 1.2-fold higher towards RebE and 2-fold higher towards rebaudioside D (RebD) than wild-type UGT76G1. RebM (12.8 ± 0.6 g/L) and RebD (10.5 ± 0.1 g/L) were generated from RebE (20 g/L) catalyzed by the S195Q mutant coupling with a sucrose synthase from Micractinium conductrix at 40 °C for 32 h. This work would expand the application of structure-based enzyme design for glycosyltransferase engineering.